The Effect of Job Crafting on Work Performance of Universities Employees - Tabinda Zainab; Dr. G. Zainab Sherazi; Dr. Zunaira Fatima (Research Journal of Psychology, 2024)
The primary purpose of the present study was to investigate the influence of job crafting (JC) on the work performance (WP) of the organization’s workforce. The population of this current study comprised all teaching and non-teaching employees of the University of Sargodha, specifically drawn from five colleges: the College of Medical & Health Science, the College of Pharmacy, the College of Engineering and Technology, the Law College, and the College of Agriculture. A total of 300 employees were selected as samples using convenient sampling techniques. Data collection was conducted using two instruments. Following a thorough examination by specialists, the pilot test alongside Cronbach’s alpha was utilized to ascertain the validity and reliability of the research instrument. The researcher gathered the data through direct physical collection methods. Data were analyzed by using SPSS version 22 and descriptive statistics like mean frequency and standard deviations were used along with inferential statistics like regression analysis, correlational analysis, T-tests, and ANOVA. The study’s findings indicated a statistically significant positive correlation between job crafting and work performance. A rather tenuous positive correlation exists between job crafting (JC) and work engagement (WE) among university employees.